Loneliness‧Autopsy - Chen, Kehua, 1961- (Book collections on Project MUSE., 2019)
Drawn from Hong Kong International Poetry Nights 2011, Loneliness * Autopsy is a chapbook of poetry by Chen Ko Hua presented in both English and Chinese. Loneliness * Autopsy is also available along with the works of other internationally renowned poets in Words and the World (Twenty-volume Set). Selected poems from this volume are featured in the anthology Words and the World: International Poetry Nights in Hong Kong.